Necesidad espiritual de amar: y ser amado al final de la vida (Theological Kronos, 2018)
This article offers a response to the question of why the spiritual need of the dying to love and to be loved until the end is considered to be the most basic of spiritual needs and the one that includes all the others. From the palliative care field, the concept and description of the spiritual needs of the dying is revisited, in addition to the process of death and dying. Other concepts come from the field of psychology: spirituality, love, and suffering. Based on the concepts of love and suffering, a final reflection is developed regarding the role of love in the dying process.
Keywords: love, death, spiritual needs of the dying, need for love and to be loved, suffering